Scientific Literature Review (SLR) of Agility Management on Organization Performance in Case of Ethiopia - Wako Jio; Kero, Chalchissa Amentie (RADINKA JAYA UTAMA PUBLISHER, 2024)
Adeniji, C., Adeyeye, O., Iyiola, O., Olokundun, M., Borishade, T., Falola, H., & Salau, O. (2018). Data on the impact of technological change on employees’ cognitive attitude and organizational performance. Data in Brief, 18, 1360–1364. https://doi.org/10.1016/j.dib.2018.04.024 Akparep, J. Y., Jengre, E., & Mogre, A. A. (2019). The Influence of Leadership Style on Organizational Performance at TumaKavi Development Association, Tamale, Northern Region of Ghana. Open Journal of Leadership, 08(01), 1–22. https://doi.org/10.4236/ojl.2019.81001 Akunne, C. S., & Ibrahim, U. A. (2021). An Evaluation of the Impact of Change Management on Employee Performance in the Nigerian Electricity Regulatory Commission. Open Journal of Business and Management, 09(05), 2591–2604. https://doi.org/10.4236/ojbm.2021.95142 AlNuaimi, B. K., Kumar Singh, S., Ren, S., Budhwar, P., & Vorobyev, D. (2022). Mastering digital transformation: The nexus between leadership, agility, and digital strategy. Journal of Business Research, 145, 636–648. https://doi.org/10.1016/j.jbusres.2022.03.038 Andriansyah, Nurwanda, A., & Rifai, B. (2023). Structural Change and Regional Economic Growth in Indonesia. Bulletin of Indonesian Economic Studies, 59(1), 91–117. https://doi.org/10.1080/00074918.2021.1914320 Carvalho, A. M., Sampaio, P., Rebentisch, E., McManus, H., Carvalho, J. Á., & Saraiva, P. (2023). Operational excellence, organizational culture, and agility: Bridging the gap between quality and adaptability. Total Quality Management & Business Excellence, 34(11–12), 1598–1628. https://doi.org/10.1080/14783363.2023.2191844 Chummun, B. Z., & Nleya, L. (2023). The Effect of Employee Involvement in Strategic Change on the Performance of Insurance Companies in Zimbabwe. Journal of Risk and Financial Management, 16(9), 409. https://doi.org/10.3390/jrfm16090409 Felipe, C., Roldán, J., & Leal-Rodríguez, A. (2017). Impact of Organizational Culture Values on Organizational Agility. Sustainability, 9(12), 2354. https://doi.org/10.3390/su9122354 Fulea, M., Mocan, B., Dragomir, M., & Murar, M. (2023). On Increasing Service Organizations’ Agility: An Artifact-Based Framework to Elicit Improvement Initiatives. Sustainability, 15(13), 10189. https://doi.org/10.3390/su151310189 Gunawan, A., Wahyuni, N., Baridzualdi, B., Katili, P. B., Setiawan, H., & Yulianti, N. (2022). Effect of job satisfaction, employee engagement, and work culture on employee performance during the COVID-19 pandemic. Journal of Systems Engineering and Management, 1(1), 29. https://doi.org/10.36055/joseam.v1i1.17542 Hutter, K., Brendgens, F.-M., Gauster, S. P., & Matzler, K. (2023). Scaling organizational agility: Key insights from an incumbent firm’s agile transformation. Management Decision. https://doi.org/10.1108/MD-05-2022-0650 Lill, P. A., & Wald, A. (2021). The agility-control-nexus: A levers of control approach on the consequences of agility in innovation projects. Technovation, 107, 102276. https://doi.org/10.1016/j.technovation.2021.102276 Lin, J. Y. (2019). Structural change and poverty elimination. China Agricultural Economic Review, 11(3), 452–459. https://doi.org/10.1108/CAER-08-2018-0169 Pettit, K. L., Balogun, J., & Bennett, M. (2023). Transforming Visions into Actions: Strategic change as a future-making process. Organization Studies, 44(11), 1775–1799. https://doi.org/10.1177/01708406231171889 Qalati, S. A., Zafar, Z., Fan, M., Sánchez Limón, M. L., & Khaskheli, M. B. (2022). Employee performance under transformational leadership and organizational citizenship behavior: A mediated model. Heliyon, 8(11), e11374. https://doi.org/10.1016/j.heliyon.2022.e11374 Rani, I. H., Kasali, R., Kusumastuti, R. D., & Hati, S. R. H. (2024). Unlocking continuous organizational agility: Proposing a model through the insight from the Indonesian banking context. Cogent Business & Management, 11(1), 2331633. https://doi.org/10.1080/23311975.2024.2331633 Rawashdeh, A., Abdallah, A. B., Alfawaeer, M., Al Dweiri, M., & Al-Jaghbeer, F. (2024). The Impact of Strategic Agility on Environmental Sustainability: The Mediating Role of Digital Transformation. Sustainability, 16(3), 1338. https://doi.org/10.3390/su16031338 Rumanti, A. A., Rizana, A. F., & Achmad, F. (2023). Exploring the role of organizational creativity and open innovation in enhancing SME performance. Journal of Open Innovation: Technology, Market, and Complexity, 9(2), 100045. https://doi.org/10.1016/j.joitmc.2023.100045 Tarba, S. Y., Frynas, J. G., Liu, Y., Wood, G., Sarala, R. M., & Fainshmidt, S. (2023). Strategic agility in international business. Journal of World Business, 58(2), 101411. https://doi.org/10.1016/j.jwb.2022.101411 Vrontis, D., Belas, J., Thrassou, A., Santoro, G., & Christofi, M. (2023). Strategic agility, openness, and performance: A mixed method comparative analysis of firms operating in developed and emerging markets. Review of Managerial Science, 17(4), 1365–1398. https://doi.org/10.1007/s11846-022-00562-4